The Circle : a novel - Eggers, Dave. (New York : Alfred A. Knopf, a division of Random House LLC ; San Francisco : McSweeney's Books, 2013)
Mae Holland, hired to work for the Circle, the world's most powerful internet company, feels she's been given the opportunity of a lifetime, but begins to suspect that the Circle is going too far in its desire to make the world a better and safer place.
"This is a Borzoi book."--Title page verso.
Keywords: Futurism -- Fiction; Electronic surveillance -- Fiction; Memory -- Fiction; Privacy -- Fiction; Social media -- Fiction; Internet industry -- Fiction; Technology -- Fiction; Humorous fiction; Satirical fiction